Substitution of the president of the republic – theoretical and terminological framework, regulation and application in comparative law - Samir Vrabec (Zbornik Radova Pravnog Fakulteta u Splitu, 2013)
Significance of the president of the republic office, even in ’smallest’ volume as of ceremonial representative of state, implicate necesity for constitutional regulation and due implementation of the substitution of president. Substitution of president means constitutionaly arranged devolution of presidential powers and duties (or even the office itself) to specific state officer in stipulated cases (death, resignation, removal from office, temporary or permanent disability) and procedure. Author made review of constitutional regulation of this matter in states with constitutional systems of paradigmatical character regarding organisation of government models. He founds diversities from non presence of vice president office, in parliamentary and semi – presidential system states, which existence solves this issue in easiest manner in presidential system, necesity for (non)election of new president, to the presidential succession line of officers or state bodies and it’s lenght. Comparation of constitutional solutions leads to conclusions about efficiency of solving this constitutional matter in individual government model in correlation to importance and widht of powers and duties which are assigned to president of the republic in respective constitutional system.